Fundamentals of Entrepreneurship (ENT300) : Business Opportunity - Qushantek Makeover Service / Sharon Livan Ujang … [et al.] - Ujang, Sharon Livan; Jerry, Jane Effarenda; James, Vivian Urai; Samshulhana, Muhamad Shafiq (2019)
When we run a company, it is easy to think that the only way to suceed is to moving forward to the expenses. Unsatisfied human and customers desires that motivate their actions and enhance fulfillment when met. Many business marketing department pay close attention to the need and want of their target market since both drive consumer purchases. These can be further described as those need and wants. Basically needs define as require (something) because it is essential or very important rather than just desirable. For example in our personal life, we need food, water, shelter, clothing and also medical. While wants is define as have a desire to possess or do something or wish for something that we do not need to survive. It is often fall in the category of luxuries which nice to have but by no means will make us suffer in any way. For example if our needs to look neat, good and ready so our wants is to makeover our self. Every consumer will have different perception on their wants. Hence, knowing the needs of the consumers and know how to fulfill those needs is a must for a business to provide good services. 10 As for our business opportunity, we decided more to focus on makeover to fulfill the requirement for need and more to wants of the consumers. Makeover play important role in our daily life. People are often wearing makeup to look ready, neat and to enhance their confidence level so that they always look good and ready for their daily life. Thus, we planned to open a makeover service business in UITM Campus Samarahan 2 that specializes in makeup, facial and grooming services. Based in our observation, there is no makeover service. This business is convenience and affordable in price which is suitable for students. Since that it is in the campus so the population is the students.